Remarks about inverse diffraction problem - Ramm, Alexander G. (My University, 1998)
From the scattering data one finds the support function or the principal curvatures of the surface of a reflecting obstacle. From either of these data the surface is effectively reconstructed.
Keywords: Inverse diffraction